ANALISIS KESALAHAN PENULISAN HURUH HANZI BAHASA MANDARIN OLEH PEMBELAJAR PEMULA DI PURWOKERTO - Nunung Supriadi (Jurnal Lingua Idea, 2018)
This research is titled " Error Analysis of Writing Chinese Letter by Learners in Purwokerto". the purpose of the research is to improve the students' competence in mastering Mandarin properly. This study focuses on the errors of Chinese Hanzi letters written by the students in learning Mandarin. especially on the order of writing mandarin strokes. The purpose of the study is to show the errors of Chinese letters by students in Purwokerto and explain the factors that cause the errors of writing letters mandarin. Data were collected using interview technique, observation, collecting of student task result. Data from the students were analyzed using Error Analysis from Corder (1976). then compared with mandarin standard based on bihuan bishuan which was made by Suparto (2003) and Song (2001).